Dapagliflozin compared with other oral anti‐diabetes treatments when added to metformin monotherapy: a systematic review and network meta‐analysis. Issue 5 (16th December 2013) - Goring, S.; Hawkins, N.; Wygant, G.; Roudaut, M.; Townsend, R.; Wood, I.; Barnett, A. H.
Abstract Aims Indirect evidence from randomized controlled trials (RCTs) was used to estimate the effect of dapagliflozin, a new agent with a novel mechanism of action (SGLT‐2 inhibition), relative to other anti‐diabetes therapies after 1 year of treatment. Methods A systematic literature review and Bayesian network meta‐analysis (NMA) of RCTs involving anti‐diabetes treatments added to metformin were conducted. RCTs enrolling subjects with type 2 diabetes inadequately controlled on metformin monotherapy were included. Comparators included dipeptidyl peptidase‐4 (DPP‐4) inhibitors, thiazolidinediones (TZDs), sulphonylureas, glucagon‐like peptide‐1 (GLP‐1) analogues and dapagliflozin. Outcomes of interest were mean change from baseline HbA1c, weight and systolic blood pressure, and incidence of hypoglycaemia. Results From 4270 abstracts, six RCTs were included in the primary analysis; no RCTs involving GLP‐1 analogues met primary inclusion criteria. All RCTs were actively controlled with sulphonylureas. The mean change in HbA1c from baseline was similar across comparators. The treatment effect (95% credible interval) of dapagliflozin on HbA1c was −0.08% (−0.25, 0.10) relative to DPP‐4 inhibitors, −0.02% (−0.24, 0.21) relative to TZDs and 0.00% (−0.16, 0.16) relative to sulphonylureas. Non‐sulphonylureas showed significantly lower risk of hypoglycaemia relative to sulphonylureas. Dapagliflozin had a significant effect on weight change: the relative difference was −2.74 kg (−5.35, −0.10) compared with DPP‐4 inhibitors, and −4.67 kg (−7.03, −2.35) compared with sulphonylureas. Systolic blood pressure was not meta‐analysed due to infrequent reporting. Conclusion Compared with DPP‐4 inhibitors, TZDs and sulphonylureas, dapagliflozin offers similar HbA1c control after 1 year, with similar or reduced risk of hypoglycaemia and the additional benefit of weight loss, when added to metformin.